DEVELOPING ASEAN AUTOMOTIVE INDUSTRY’S FRAMEWORK USING BUSINESS INTELLIGENCE APPROACH - Amin, Abdusy Syakur; Hermina , Tinneke (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This research investigates the potential of Business Intelligence Technology (BIT) to enhance the sustainability of the ASEAN automotive industry in the context of Society 5.0.  Employing qualitative methods like focus groups, interviews, and document analysis, we developed a framework for leveraging BIT to address the challenges of balancing market demands with sustainability goals. Findings reveal that BIT empowers ASEAN nations to understand market dynamics, analyze consumer preferences for sustainable options, and explore market potential.  However, the framework necessitates acknowledging and mitigating the environmental impact of industry practices to align with evolving consumer priorities.  This research contributes valuable insights for policymakers and industry leaders in fostering a more sustainable automotive industry within ASEAN.